Experimental studies of instability process and energy evolution of tunnels under true triaxial stresses: The role of pre-existed flaws - Li, Binglei; Li, Jianing; Hu, Hongyuan; Gong, Jinrui; Luo, Tao (Frontiers in Earth Science, 2023)
In the natural geological environment, there are many joints, faults and cavities. These natural defects will have an impact on the stability of tunnels. This paper investigates different conditions of surrounding rock: intact surrounding rock, surrounding rock with open-flaw and surrounding rock with filled-flaw. Under the true triaxial test. The effect of different surrounding rock conditions on the internal failure characteristics of tunnel under true triaxial conditions is explored. According to the characteristics of energy evolution and chaos theory, the damage inside the tunnel is divided into stages. The results show that: (1) he failure characteristics in the tunnel are different for different surrounding rock conditions they do not represent the stability of the surrounding rock of the tunnel; (2) The trend of energy dissipation is different under different surrounding rock conditions. The elastic stage of the surrounding rock is shortened and the dissipation energy shows an earlier upward trend as its integrity declines. (3) When analysing the tunnel, chaos theory can give early warnings about the instability of the surrounding rock, but it can not give early warning of particle spray and spalling inside the tunnel.